Cuprous-Catalyzed Cross-Coupling Reaction of Grignard Reagents with Alkyl Halides - Dai, Z.Q.; Zhang, W.W.; Zhang, Z.Y.; Wei, B.M.; Yang, Y.K. (Asian Journal of Chemistry, 2011)
For the first time in the presence of a catalytic amount of cuprous iodide, alkyl bromide reacted with aryl magnesium bromide (Grignard reagent) to obtain the cross-coupling product in good yields. The conditions of the cross-coupling reaction were studied. The suitable amount of catalyst, reaction temperature and time are 2 % mol (based on alkyl halide), 67 ºC (reflux), 6 h, respectively. Under the optimal conditions, the yields of the cross-coupling could reach up to 90 %. Moreover, Grignard reagent with an electron-rich group reacted rapidly and with an electronwithdrawing group reacted sluggishly.